(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2010)
The aim of the paper was to discuss the trends in the analysis of static balance and relation between physiological parameters and characteristics of posturograms. Static balance is ability to keep steady posture in certain stance [2, 3]. Posturography is one of most popular research methods of static balance [10, 11]. During the last decade it was maintained that the most informative dependent variables defining postural stability were the amplitude of the center of foot pressure (COP) sway in anterior-posterior and mediolateral directions, the length of the COP pathway and the area of the COP sway [9, 15]. The output of the posturograms registered during quiet standing is irregular and erratic [14]. Therefore, methods analyzing the structure of the posturograms are very topical for physiology and Rehabilitation science. The scientists attempt to determine certain noise and oscillation patterns in the posturogram [20]. According to researchers [14], the structure and roughness or smoothness of the posturogram could reflect the changes in postural control system. It is still questionable which of the methods analyzing the posturogram outcomes could be the most informative and useful for the diagnostics of postural control disorders. It is important to be able to repeat the scientific study, but it is still complicated to solve tasks related to postural control disorders diagnostics and the evaluation of the treatment means effectiveness. It is important to define the relation between physiological parameters and characteristics of posturograms in order to apply the posturography for balance disorders diagnostics. We suppose that methods of posturogram structure analysis could improve the differential balance disorders diagnostics essentially. Keywords: static balance, static posturography, center of foot pressure.